Left ventricular-aortic angle is associated with platelet reactivity in patients with aortic stenosis. Issue 6 (22nd September 2022) - Mourikis, Philipp; Zako, Saif; Dannenberg, Lisa; M'Pembele, Rene; Hohlfeld, Thomas; Zeus, Tobias; Kelm, Malte; Veulemans, Verena; Polzin, Amin
Abstract : The impact of aortic stenosis on platelet reactivity is unclear. Previous studies reported contradicting results. The reason for this is unknown. It is known that flow alterations enhance platelet reactivity. A steep left ventricular-aortic angle (LV-AO-angle) is associated with turbulent flow in the aorta ascendens. Therefore, in this study, we hypothesized that LV-AO-angle is associated with platelet reactivity in patients with severe aortic stenosis. We included 289 patients with severe aortic stenosis and performed cardiac computertomography to assess the LV-AO-angle. Platelet function was evaluated by light transmission aggregometry. Platelet reactivity was higher in patients with a steep LV-AO-angle (ADP: <160°: 66.99% ± 20.72% vs. ≥160°: 60.66% ± 19.85%, P = 0.009; collagen: <160°: 78.67% ± 13.19% vs. ≥160°: 73.85% ± 14.44%, P = 0.003). Using Spearman correlation, ADP and collagen-induced aggregation was associated with LV-AO-angle (ADP: r = −0.19, P = 0.0009, R 2 = 0.022; collagen: r = −0.21, P = 0.0004, R 2 = 0.027). Apart from platelet reactivity, body weight, history of myocardial infarction and other factors were associated with steep LV-AO-angle. However, multivariate cox-regression (including body weight, comorbidities, history of MI and cardiac surgery, kidney function and laboratory parameters) revealed that LV-AO angle was a robust predictor of ADP and collagen-induced platelet aggregation. Steep LV-AO-angle is associated with enhanced platelet reactivity in patients with aortic stenosis. This could be the reason of contradicting results regarding platelet function in patients with aortic stenosis in previous studies. In addition, enhanced platelet reactivity in steep LV-AO-angle aortic stenosis patients might be a promising target in pathogenesis of aortic stenosis.